A princess by Christmas - London, Julia (London, Julia. Royal wedding., 2020)
Working with Marek Brendan, the heir to the Weslorian throne, to stop a coup involving her sister and her husband, the crown prince of Alucia, reporter Hollis Honeycutt, as things take a romantic turn, must choose between duty and love.